Countries of a Feather flock together - Charles van Marrewijk; Gus Garita (Tinbergen Institute, 2008)
We analyze the economic forces underlying cross-border Mergers and Acquistions (M&As) using a large bilateral panel data set. The frequent occurrence of zero observations provides essential information on the structure of M&A flows, which we model empirically using a two-stage procedure. At the fist stage, an observation is either classified in the Passive Group (always zero) or in the (potentially) Active Group using a logit model. At the second stage, the size of M&A flows in the Active Group is modeled using a gravity-type negative binomial model. We find that: (i) market size (GDP) of both acquirer and target is more important for trade flows than for cross-border M&As, (ii) market development (per capita GDP) is more important for cross-border M&As than for trade flows, (iii) for M&As, the target's market, both in size and development, is more important than the acquirer's market, and (iv) the impact of distance is larger on trade flows than for M&As. Financial openness is a prerequisite for becoming active in M&As and positively influences the size of M&A flows. Our estimates on the direction, size, and significance of the main variables are robust for alternative specifications, incorporating lagged stock market value, black market premium, real interest rates, transparency, and exchange rate variability. Finally, we provide additional support and extend the recent results of Blonigen et al. (2007) on outside-market potential and of Bergstrand and Egger (2007) on Rest of World GDP.
Keywords: E2; E6; F4; G15; G34; 330; capital flows; cross-border mergers & acquisitions; foreign direct investment; financial openness; Kapitalmobilität; Übernahme; International; Auslandsinvestition; Finanzmarktregulierung; Welt